1986
DOI: 10.1523/jneurosci.06-04-01194.1986
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of thyrotropin-releasing hormone immunoreactivity in neurons of the mouse spinal dorsal horn

Abstract: Thyrotropin-releasing hormone-like immunoreactivity was demonstrated in neurons within the superficial laminae (I, II, III) of the mouse spinal dorsal horn by light-microscopic peroxidase immunocytochemistry. The immunoreactivity was distributed in a narrow dorsoventral band that enclosed the substantia gelatinosa (lamina II), with a higher concentration along the lamina II/III border. At present, the functional significance of these neurons is unknown. Their existence within the substantia gelatinosa suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…The number and the intensity of TRH-IR fibers in the dorsal horn decreased considerably after the combination of SCT and dorsal rhizotomy. This was unexpected since such fibers have been claimed to have a segmental origin (Coffield et al, 1986;Harkness and Brownfield, 1986;Ulfhake et al, 1987) and no TRH-LI has been detected in dorsal root ganglia as shown here (in L, and S, <3 pg/mg protein) and in previous studies (Garry et al, 1989) by use ofRIA. This novel interesting finding is being subjected to further study in our laboratory (Ulfhake et al, in preparation).…”
Section: Lesion Experimentssupporting
confidence: 43%
“…The number and the intensity of TRH-IR fibers in the dorsal horn decreased considerably after the combination of SCT and dorsal rhizotomy. This was unexpected since such fibers have been claimed to have a segmental origin (Coffield et al, 1986;Harkness and Brownfield, 1986;Ulfhake et al, 1987) and no TRH-LI has been detected in dorsal root ganglia as shown here (in L, and S, <3 pg/mg protein) and in previous studies (Garry et al, 1989) by use ofRIA. This novel interesting finding is being subjected to further study in our laboratory (Ulfhake et al, in preparation).…”
Section: Lesion Experimentssupporting
confidence: 43%
“…In order to optimise the conditions for immunohistochemical visualisation of 5HT-LI, we have used Zamboni's fixative (Zamboni and De Martino, 1967). However, it has been known for some time that adding small amounts of glutaraldehyde (0.245%; Willingham, 1983) gives a much more "complete" staining of TRH-LI probably due to increased retention of this small peptide (Coffield et al, 1986;Harkness and Brownfield, 1986;Tsuruo et al, 1987;Ulfhake et al, 1987) than the fixative used here. However, the ventral horn terminals, which probably contain fairly high concentrations of TRH, can be visualized with a high degree of reproducibility even without glutaraldehyde as shown previously and here.…”
Section: Methodological Considerationsmentioning
confidence: 88%
“…In contrast, in the dorsal horn immunohistochemical studies have shown that these neuropeptides are not co-localised with 5HT (Arvidsson et al, 1990;Tashiro and Ruda, 1988;Tuchscherer et al, 1987;Wessendorf and Elde, 1987). Instead they are found in primary afferents (SP and galanin) and neurons intrinsic to the spinal cord (SP, TRH, and galanin) (Arvidsson et al, 1990Coffield et al, 1986;Harkness and Brownfield, 1986;Ljungdahl et al, 1978;Melander et al, 1986;Tessler et al, 1980Tessler et al, , 1981Tessler et al, , 1984Ulfhake et al, 1987). Thus, the decline in SP-and TRH-LI in the dorsal quadrants suggests that primary afferents andlor intrinsic systems suffer a decline in peptide content of the same magnitude as the 5HT bulbospinal system, although a larger SP decrease in the sensory afferents could disguise a lack of effect on bulbospinal fibers.…”
Section: Serotoninergic Bulbospinal System In the Aged Ratmentioning
confidence: 99%
“…Thyrotropin-releasing hormone (TRH) immunoreactivity is present in a number of locations throughout the mammalian central nervous system (Brownstein et al, 1974;Winokur and Utiger, 1974; Hokfelt et al, 1975a,b;Johansson et al, , 1981Bowker et al, 1983;Lechan et al, 1983;Coffield et al, 1986; Harkness and Brownfield, 1986a,b;Tsuruo et al, 1987;Merchenthaler et al, 1988;Poulat et al, 1992). Varicose TRH-immunoreactive nerve terminals are found in the vicinity of many groups of motoneurons throughout the length of the spinal cord (Hokfelt et al, 1975a,b;Johansson et al, 1981;Lechan et al, 1983; Harkness and Brownfield, 198613;Ulfhake et al, 1987;Merchenthaler et al, 1988;Poulat et al, 1992).…”
Section: Indexing Terms: Cholera Toxin B Subunit Electron Microscopymentioning
confidence: 99%